Modified aminosilane copolymer, silicon nitride etching solution, preparation method and application
By designing the modified aminosilane copolymer and preparing the silicon nitride etching solution, the problem of low selectivity of the existing silicon nitride etching solution during the etching process is solved, and high selectivity etching of Si3N4/SiO2 and Si3N4/polysilicon is achieved. , significantly improves the performance of the etching liquid.
Patent Information
- Application Number
- CN202411415379.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing silicon nitride etching solution has relatively low etching choices for Si3N4/SiO2 and Si3N4/polysilicon during the etching process.
A modified aminosilane copolymer was designed, and the copolymer was prepared by the steps of transesterification reaction and alcohol ammonia reaction, and used to prepare the silicon nitride etching liquid. The copolymer is composed of phenylacetylene and modified aminosilane, and has an excellent etch selection ratio.
By using the silicon nitride etching solution containing modified aminosilane copolymer, the etching selection ratio of Si3N4/SiO2 and Si3N4/polysilicon can be significantly improved, effectively suppressing silicon oxide etching and polysilicon corrosion.
Smart Images

Figure CN118909190B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of etching liquid, and in particular relates to a modified aminosilane copolymer, a silicon nitride etching liquid, a preparation method and an application thereof. Background Art
[0002] 3D NAND flash memory devices have been developed that increase non-volatile storage density by vertically stacking memory cells. In the manufacturing process of 3D NAND flash memory, multiple layers of silicon nitride (Si3N4) and silicon oxide (SiO2) are first deposited alternately, and then dry etching and polysilicon deposition are completed. Finally, the silicon nitride layer is completely etched laterally by high-temperature phosphoric acid (H3PO4) and then the memory cell is constructed. When the silicon nitride layer is laterally etched in H3PO4, not only will the silicon oxide layer be etched, causing the silicon oxide layer to become thinner, but also, as the silicon nitride layer is continuously etched laterally, the deposited polysilicon layer will be exposed in the later stage of etching, and the polysilicon will also be corroded when placed in a phosphoric acid environment.
[0003] Therefore, it is necessary to develop a high selectivity silicon nitride etching solution that can inhibit silicon oxide etching and polysilicon corrosion. Summary of the invention
[0004] The technical problem solved by the present invention is that the etching selectivity of silicon nitride etching solution to Si3N4 / SiO2 and Si3N4 / polysilicon is relatively low during the etching process.
[0005] In view of the technical problems existing in the prior art, the present invention designs a modified aminosilane copolymer, a silicon nitride etching solution, and a preparation method and application thereof.
[0006] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising" and similar meanings, and closed-ended "consisting of..." and similar meanings.
[0007] In order to solve the above-mentioned technical problems, the present invention adopts the following solutions:
[0008] [The first technical solution]
[0009] In the first aspect, a technical solution of the present invention is to provide a modified aminosilane. In the present invention, the modified aminosilane has a general formula of C5H6O-N(CH2)3Si(OR)3.
[0010] Where R is C m H 2m+1 , m is 1 or 2.
[0011] Furthermore, m is preferably 1.
[0012] Furthermore, the modified aminosilane has two structures of Formula 1 or Formula 2, which are as follows:
[0013] .
[0014] [Second technical solution]
[0015] In a second aspect, a technical solution of the present invention is to provide a method for preparing the modified aminosilane.
[0016] The preparation method of the modified aminosilane specifically comprises the following steps:
[0017] S1: Transesterification reaction: Using methanol as solvent and sodium methoxide as catalyst, α,β-unsaturated valerolactone and its isomers and aminosilane are transesterified at 50-70°C;
[0018] S2: Alcohol-ammonia reaction: Ni is added as a catalyst to the product obtained in step S1, and the alcohol-ammonia reaction is carried out at 100-200° C. and 0.5-10 MPa to obtain the modified aminosilane.
[0019] Furthermore, the transesterification reaction time in step S1 is 1-4 hours.
[0020] Furthermore, the transesterification reaction time in step S1 is preferably 2 h.
[0021] Furthermore, in step S2, the alcohol-ammonia reaction time is 1-4 hours.
[0022] Furthermore, the alcohol-ammonia reaction time in step S2 is preferably 2 h.
[0023] Furthermore, the α,β-unsaturated valerolactone and its isomers in step S1 are α,β-unsaturated δ-valerolactone or α,β-unsaturated γ-valerolactone.
[0024] Furthermore, the α,β-unsaturated valerolactone and its isomers in step S1 are α,β-unsaturated γ-valerolactone or α,β-unsaturated δ-valerolactone.
[0025] Furthermore, the aminosilane in step S1 is 3-aminopropyltrimethoxysilane or 3-aminopropyltriethoxysilane.
[0026] Furthermore, the aminosilane in step S1 is preferably 3-aminopropyltrimethoxysilane.
[0027] Furthermore, in step S1, the molar ratio of α,β-unsaturated valerolactone and its isomers to aminosilane is 1:0.5-2.
[0028] Furthermore, in step S1, the molar ratio of α,β-unsaturated valerolactone and its isomers to aminosilane is preferably 1:1.
[0029] Furthermore, in step S1, the molar amount of the catalyst sodium methoxide is 0.5-3% of methanol.
[0030] Furthermore, the mass of the catalyst Ni in step S2 accounts for 0.5-3wt% of the reaction product in step S1.
[0031] Furthermore, in step S1, the molar amount of the catalyst sodium methoxide accounts for 1% of methanol.
[0032] Furthermore, the mass of the catalyst Ni in step S2 accounts for 0.8wt% of the reaction product in step S1.
[0033] [The third technical solution]
[0034] In a third aspect, a technical solution of the present invention is to provide a modified aminosilane copolymer.
[0035] Furthermore, the modified aminosilane copolymer is formed by copolymerization of phenylacetylene and modified aminosilane, and the structural formula of the modified aminosilane copolymer is Formula 3 or Formula 4:
[0036] .
[0037] Where R is C m H 2m+1 , m is 1 or 2, and n represents the degree of polymerization.
[0038] Furthermore, m is preferably 1, and n is preferably an integer of 2-50.
[0039] [The fourth technical solution]
[0040] In a fourth aspect, a technical solution of the present invention is to provide a method for preparing the modified aminosilane copolymer.
[0041] The preparation method of the modified aminosilane copolymer specifically comprises the following steps:
[0042] (1) Preparation of modified aminosilane;
[0043] (2) Preparation of modified aminosilane copolymer:
[0044] The modified aminosilane copolymer was synthesized by solution polymerization with acetone as solvent, n-butyl lithium as initiator, phenylacetylene and modified aminosilane as polymerization monomers.
[0045] Further, in step (2), the polymerization temperature is -78°C to -80°C, and the reaction time is 2-8h;
[0046] Furthermore, in step (2), the polymerization reaction time is preferably 5 h.
[0047] Further, in step (2), the molar amount of phenylacetylene is 7-8 moles;
[0048] Further, in step (2), the molar amount of the modified aminosilane is 7-8 moles;
[0049] Furthermore, in step (2), the molar ratio of phenylacetylene to modified aminosilane is 1:0.5-2.
[0050] Furthermore, in step (2), the molar ratio of phenylacetylene to modified aminosilane is preferably 1:1.
[0051] Furthermore, in step (2), the molar amount of the initiator n-butyl lithium is 0.5-1 mole.
[0052] Furthermore, in step (2), the molar amount of the solvent acetone is 10-20 moles.
[0053] [Fifth technical solution]
[0054] In a fifth aspect, a technical solution of the present invention is to provide use of the modified aminosilane copolymer in a 3D flash memory chip.
[0055] The inventors have found that the modified aminosilane copolymer can be used in silicon nitride etching solution for 3D flash memory chips. By including the modified aminosilane copolymer, the silicon nitride etching solution has an excellent etching selectivity ratio.
[0056] [Sixth technical solution]
[0057] In the sixth aspect, a technical solution of the present invention is to provide a silicon nitride etching solution containing a modified aminosilane copolymer, the components of which include a modified aminosilane copolymer, concentrated phosphoric acid and ultrapure water; the mass ratio of the modified aminosilane copolymer, concentrated phosphoric acid and ultrapure water is 0.5-5:75-85:12-15.
[0058] The ultrapure water is deionized water with a resistance of ≥ 18 MΩ.
[0059] [Seventh technical solution]
[0060] In a seventh aspect, a technical solution of the present invention is to provide a method for preparing the above-mentioned silicon nitride etching solution, wherein the preparation method is specifically:
[0061] Step 1: Weigh each component in its respective amount;
[0062] Step 2: Ultrapure water and modified aminosilane copolymer are slowly added to concentrated phosphoric acid in sequence, and the temperature is slowly raised to 80° C.-100° C. under stirring to obtain the silicon nitride etching solution.
[0063] [Eighth Technical Solution]
[0064] In an eighth aspect, a technical solution of the present invention is to provide the use of the silicon nitride etching solution for etching the silicon nitride layer in a 3D flash memory chip.
[0065] [Ninth technical solution]
[0066] In a ninth aspect, a technical solution of the present invention is to provide an etching method of the silicon nitride etching solution, comprising the following steps:
[0067] Step 1: Use the silicon nitride etching solution to soak the silicon nitride wafer at 157°C-160°C. The etching device is sealed to prevent water evaporation. The soaking time is determined according to the thickness of the etching required;
[0068] Step 2: Rinse the soaked silicon nitride sample in ultrapure water at least twice, thus completing the silicon nitride wafer rinsing step;
[0069] Step 3: Quickly dry the surface with a nitrogen gun.
[0070] The present invention provides a modified aminosilane copolymer, a silicon nitride etching solution, a preparation method and application thereof, which have the following beneficial effects:
[0071] 1. Since terminal olefins usually have high reactivity, the C=C bond of olefins is easy to break and react or undergo a certain degree of polymerization under high temperature and acidic conditions. The present invention copolymerizes phenylacetylene with modified aminosilane so that the vinyl group no longer acts as a terminal olefin and can be stably retained in the copolymer.
[0072] 2. The modified aminosilane copolymer of the present invention has three alkoxy groups connected to Si atoms and easily hydrolyzed. The groups can be hydrolyzed under acidic conditions to generate Si-OH bonds. The Si-OH bonds can be tightly combined with the silicon dioxide layer through van der Waals forces, thereby adhering to and wrapping the silicon dioxide layer to inhibit silicon dioxide etching and improve the Si3N4 / SiO2 selectivity; the vinyl group can be protonated to make itself positively charged. Since the polysilicon surface is electronegative, the two can interact electrostatically, thereby protecting the polysilicon surface and improving the Si3N4 / polysilicon selectivity.
[0073] 3. The silicon nitride etching solution containing the modified aminosilane copolymer of the present invention can maintain a relatively high etching selectivity ratio for both silicon dioxide and polysilicon.
[0074] Therefore, the silicon nitride etching solution of the present invention has very good application prospects and large-scale industrial promotion potential in the field of 3D flash memory chip silicon nitride etching solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 : is the infrared spectrum of the modified aminosilane copolymer prepared in Preparation Example 6. DETAILED DESCRIPTION
[0076] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings:
[0077] About the preparation method of the preparation example of the modified aminosilane of the present invention:
[0078] S1: Transesterification reaction: using methanol as solvent and sodium methoxide as catalyst, α,β-unsaturated valerolactone and its isomers and aminosilane are transesterified at 60°C for 2h; the molar amount of the catalyst sodium methoxide is 0.2 mol (i.e., the molar amount of the catalyst sodium methoxide accounts for 1% of the molar amount of methanol), and the amount of methanol added is 20 mol;
[0079] S2: Alcohol-ammonia reaction: Ni accounting for 1 wt% of the product is added as a catalyst to the product obtained in step S1, and the alcohol-ammonia reaction is carried out at 150° C. and 6 MPa for 2 h to obtain the modified aminosilane.
[0080] Table 1: Modified aminosilane preparation examples 1 to 5
[0081]
[0082] The synthesis method of the modified aminosilane copolymer preparation examples 6-10 involved in the present invention is as follows:
[0083] Using 15 mol of acetone as solvent, 0.8 mol of n-butyl lithium as initiator, polymerization temperature -78 ° C, 7 mol of phenylacetylene and 7 mol of modified aminosilane in Preparation Example 1-5 as polymerization monomers (i.e., the molar ratio of phenylacetylene to modified aminosilane is 1:1), a solution polymerization method was used to synthesize modified aminosilane copolymers. The reaction was continued for 5 hours. After the phenylacetylene and the modified aminosilane in Preparation Example 1-5 reacted, modified aminosilane copolymers in Preparation Examples 6-10 were obtained respectively. Among them, the structural formula of the modified aminosilane copolymer in Preparation Example 6-8 is shown in Table 2. The modified aminosilane copolymers in Preparation Examples 9-10 could not be synthesized.
[0084] Table 2: Preparation Examples 6-8 of Modified Aminosilane Copolymers
[0085]
[0086] Preparation methods of silicon nitride etching solutions of the present invention and comparative examples:
[0087] Step 1: Weigh each component in its respective amount;
[0088] Step 2: Ultrapure water and modified aminosilane copolymer are slowly added to concentrated phosphoric acid in sequence, and the temperature is slowly raised to 80° C. under stirring to obtain the silicon nitride etching solution.
[0089] Table 3: Examples 1 to 3 of silicon nitride etching solutions
[0090]
[0091] Table 4: Comparative Examples 1-3 of Silicon Nitride Etching Solutions
[0092]
[0093] Table 5: Test data of Examples 1 to 3 and Comparative Examples 1 to 3
[0094]
[0095] About performance testing and description:
[0096] The method for etching silicon nitride using the above etching solution is:
[0097] Step 1: Introduce the silicon nitride etching solution into the etching tank, and use the etching solution to soak the silicon nitride sample at 160° C. The etching device is sealed to prevent water evaporation, and the soaking time is determined according to the thickness of the etching required;
[0098] Step 2: Rinse the soaked silicon nitride sample in ultrapure water at least twice, thus completing the silicon nitride wafer rinsing step;
[0099] Step 3: Quickly dry the surface with a nitrogen gun.
[0100] The test method for etching rate is:
[0101] The silicon nitride etching solution is introduced into the etching tank, and then the etching solution is used to soak the silicon nitride wafer, silicon dioxide wafer and polycrystalline silicon wafer respectively at 160°C. The thickness of the silicon nitride wafer and silicon dioxide wafer is 3000Å, and the thickness of the polycrystalline silicon wafer is 1600Å. The silicon dioxide wafer and the polycrystalline silicon wafer are soaked for 60 minutes respectively, and the film thickness before and after etching is tested by a film thickness meter and the etching rate is calculated. The etching rate of the silicon nitride wafer is calculated according to its complete etching time.
[0102] The etched silicon nitride wafer, silicon dioxide wafer and polycrystalline silicon wafer are rinsed in ultrapure water at least twice, and the etched silicon nitride wafer and silicon oxide wafer are obtained after the treatment; the film thickness before and after etching is tested by a film thickness meter and the etching rate is calculated.
[0103] The ultrapure water used in the above steps is deionized water with a resistance of at least 18 MΩ.
[0104] Analysis of the test results:
[0105] Based on Table 5, it can be seen that the amino group of Comparative Example 1 is not at the end, and cannot undergo modification reaction with α,β-unsaturated valerolactone, and further cannot undergo polymerization reaction, resulting in no protective effect on polycrystalline silicon.
[0106] Comparative Example 2 uses unmodified aminosilane and phenylacetylene, which cannot be polymerized, resulting in no protective effect on polycrystalline silicon.
[0107] Comparative Example 3 uses 3-aminopropyltrimethoxysilane, which results in no protective effect on polysilicon.
[0108] The aminosilanes used in Comparative Examples 1-3 were not successfully modified, and their protective effect on silica was weak. However, due to their certain Si-OH structure, they only had a slight effect on the protection of silica.
[0109] Further comparison is made through the attached drawings in the specification:
[0110] The modified aminosilane copolymer of Preparation Example 6 was subjected to infrared testing. The test results are shown in Figure 1 .
[0111] from Figure 1 It can be seen that 2900cm -1 and 2800cm -1 The peaks nearby are the characteristic peaks of -CH3 and -CH2, 1450 cm -1 and 1550 cm -1 The peak near the benzene ring is 1600 cm -1 Nearby is the C=C bond absorption peak, 1700 cm -1 Nearby is the C=O bond absorption peak, 1100 cm -1 The Si-O bond absorption peak is near 1300 cm -1 Nearby is the CN bond absorption peak. In summary, the modified aminosilane copolymer Preparation Example 6 has been successfully synthesized.
[0112] The present invention is described exemplarily above in conjunction with the embodiments and drawings. It is obvious that the implementation of the present invention is not limited to the above-mentioned methods. As long as various improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A modified aminosilane copolymer, characterized in that: The modified aminosilane copolymer is formed by copolymerization of phenylacetylene and modified aminosilane, and the structural formula of the modified aminosilane copolymer is Formula 3 or Formula 4: Where R is C m H 2m+1 , m is 1 or 2, n represents the degree of polymerization, and n is an integer of 2-50.
2. A method for preparing the modified aminosilane copolymer according to claim 1, characterized in that: The steps include: (1) Preparation of modified aminosilane; (2) Preparation of modified aminosilane copolymer: The modified aminosilane copolymer was synthesized by solution polymerization method using acetone as solvent, n-butyl lithium as initiator, phenylacetylene and modified aminosilane as polymerization monomers. The general formula of the modified aminosilane is C5H6O-N(CH2)3Si(OR)3, Where R is C m H 2m+1 , m is 1 or 2; The modified aminosilane has two structures, Formula 1 or Formula 2, as follows: 。 3. The method for preparing the modified aminosilane copolymer according to claim 2, characterized in that: The method for preparing the modified aminosilane described in step (1) comprises the following steps: S1: Transesterification reaction: Using methanol as solvent and sodium methoxide as catalyst, α,β-unsaturated valerolactone and its isomers and aminosilane are transesterified at 50-70°C; S2: Alcohol-ammonia reaction: Ni is added as a catalyst to the product obtained in step S1, and the alcohol-ammonia reaction is carried out at 100-200° C. and 0.5-10 MPa to obtain the modified aminosilane.
4. The method for preparing the modified aminosilane copolymer according to claim 3, characterized in that: In step S1, the molar ratio of α,β-unsaturated valerolactone and its isomers to aminosilane is 1:0.5-2.
5. A silicon nitride etching solution, characterized in that: The invention comprises the modified aminosilane copolymer according to claim 1, concentrated phosphoric acid and ultrapure water, wherein the mass ratio of the modified aminosilane copolymer, concentrated phosphoric acid and ultrapure water is 0.5-5:75-85:12-15.
6. A method for preparing the silicon nitride etching solution according to claim 5, characterized in that The following steps are involved: Step 1: Weigh each component in its respective amount; Step 2: Ultrapure water and modified aminosilane copolymer are slowly added to concentrated phosphoric acid in sequence, and the temperature is slowly raised to 80° C.-100° C. under stirring to obtain the silicon nitride etching solution.
7. A method for treating a 3D flash memory chip using the silicon nitride etching solution of claim 5, characterized in that: The steps include: Step 1: Use the silicon nitride etching solution to soak the silicon nitride wafer at 157°C-160°C. The etching device is sealed to prevent water evaporation. The soaking time is determined according to the thickness of the etching required; Step 2: Rinse the soaked silicon nitride sample in ultrapure water at least twice, thus completing the silicon nitride wafer rinsing step; Step 3: Quickly dry the surface with a nitrogen gun.
8. Use of the silicon nitride etching solution according to claim 5 in the field of 3D flash memory chips.
Citation Information
Patent Citations
Silicon-containing copolymer with phenylacetylene end group
CN101260175A
Silicon nitride etching liquid composition
CN113544822A